Competitive advantage and clusters: evidence from textile, wearing apparel, carpet, automotive, tourism, and furniture clusters in Turkey - Mutlucan, Nigar Çağla. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2015., 2013)
Though Alfred Marshall first introduced the concept of industrial district into economic thought in 1890, it was Michael Porter who elevated “the cluster” to stardom. Since then, politicians, non-governmental organizations, CEOs, consultants, and the academia have paid more attention to it. However, despite all the research and knowledge about the ability of clusters to promote innovation, regional economic development, and national prosperity, we know very little about the firms that operate from within these clusters and drive their success. Therefore, this thesis tries to answer the following research question: how do firms create and defend competitive advantages through clusters? The present thesis tries to build and test a model to explore the firm characteristics that lead to performance differences among firms. The theoretical model examines the relationships between several constructs and firm performance, namely, business ties, support ties, entrepreneurial orientation and strategic learning capability, while being moderated by the cluster construct. A survey conducted with 160 firms from nine clusters in six industries in Turkey was conducted. The results indicate that ‘entrepreneurial orientation’ and ‘support ties’ have a significant positive impact on both the profitability and the sales performance of the firms, but ‘cluster’, defined in this thesis as consisting of geographical concentration and inter-firm linkages dimensions, does not significantly moderate any of the relationships hypothesized in the theoretical model.
Keywords: Industrial districts.